First report of Athelia rolfsii (= Sclerotium rolfsii ) causing southern blight on Pachyrhizus erosus in Mexico - Terrones-Salgado, José; Ortega-Acosta, Santo Angel; Ortega-Acosta, Candelario; Rodríguez Esquivel, Marcos; Sánchez-Ruiz, Francisco Javier; Palemon, Francisco; Vallejo-Pérez, Moisés Roberto (Plant disease, 2023)
, commonly named jicama, is native to Mexico and is cultivated for its tuberous roots which are edible. In November 2021, field sampling was carried out in municipality of Huaquechula (18.748640N, 98.550817W, 1,580 m above sea level), state of Puebla, México. The disease had an incidence between 20 and 30% in approximately 10 ha. Infected plants showed wilting, yellowing foliage, rotting with white mycelium, abundant sclerotia were observed in the roots and tuber. Tuber splits transversely over time. Twenty plants with symptoms of disease were carried out to isolate the fungus. The sclerotia found in the tubers were disinfected with 3% NaOCl, rinsed twice with sterile distilled water, and excess moisture was removed and, transferred on Potato Dextrose Agar (PDA) culture medium and incubated at 28°C. Mycelial fragments from symptomatic tubers, were plated directly to PDA. Twenty representative isolates were obtained by hyphal-tip method, one for each diseased plant sampled (10 isolates from sclerotia and the other 10 from fragments of mycelium). After 10 days, colonies showed fast-growing, dense, cottony-white aerial mycelium, forming globoid to irregular sclerotia, measuring 1.0-1.7 mm in diameter (mean = 1.42 mm; n=100). The number of sclerotia produced per Petri dish ranged from 54 to 542 (mean = 274, n = 50). These sclerotia were initially white and gradually turned brown. Microscopic examination showed septate hyphae with some cells having clamp connections. Based on morphological characteristics, the fungal isolates were identified as (Curzi) CC Tu & Kimbr (Syn: ) (Mordue 1974). For molecular identification, a representative isolate (Sr.1), the ITS region was amplified (650 bp) using primers ITS1/ITS4 (White et al. 1990). The obtained sequence (GenBank: ON206899) was subjected to BLAST analysis, where it had 100% identity with isolates (GenBank: MG836252 and MH517363). Phylogenetic analysis with the neighbor-joining method in MEGAX, grouped the Sr.1 isolate into a common clade with different isolates. Pathogenicity was confirmed by inoculating 20 tubers detached from healthy variety "Criolla de Morelos", into which a portion of mycelium from the Sr.1 isolate was inserted with a sterile wooden stick at one point per tuber. In five tubers, only a sterile wooden stick was inserted as negative controls. The tubers were placed under laboratory conditions with relative humidity close to 100% and a temperature of 28°C. Symptoms like those observed in the field were observed after five days. Control tubers showed no symptoms. Additional pathogenicity tests were performed on 50 plants of 100-day-old of the variety "Criolla de Morelos", grown in pots with sterile soil. Ten sclerotia of 10 days old were deposited at the base of the stem, 10 mm below the soil surface; as control treatment only, sterile distilled water was deposited on 20 plants. The plants were placed in a greenhouse (Center for Technological Innovation in Protected Agriculture of the Popular Autonomous University of the State of Puebla), at 28 ± 1°C and 90% of temperature and relative humidity, respectively. After 15 days, all inoculated plants showed symptoms similar to those observed in the field. Control plants showed no symptoms. re-isolated from inoculated tubers and stem, fulfilling Koch's postulates. Previously, was reported in Mexico, causing southern blight on sesame (Hernández-Morales et al. 2018). To our knowledge, this is the first report of causing southern blight on in Mexico (Farr and Rossman 2022). This research is important to design management strategies and prevent its spread to other -producing areas.